2012
DOI: 10.1111/j.1095-8312.2012.01985.x
|View full text |Cite
|
Sign up to set email alerts
|

The cowl does not make the monk: scarab beetle pollination of the Neotropical aroidTaccarum ulei(Araceae: Spathicarpeae)

Abstract: Taccarum ulei (Araceae, Spathicarpeae) is a seasonal geophytic aroid, native to north‐eastern Brazil, that flowers during two months of the rainy season. Patterns of floral thermogenesis, pollination biology, and floral traits associated with pollination syndromes were studied and compared with those of other Araceae. Two species of cyclocephaline scarabs (Scarabaeidae, Cyclocephalini) were recognized as effective pollinators: Cyclocephala celata and Cyclocephala cearae. Larvae of an unidentified species of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…In contrast, only one genus, Cyclocephala, has been recorded from dicot flowers (Figure 1). Experimental and observational studies have demonstrated that cyclocephalines can act as pollinators in Nymphaeales, Magnoliales, Arecales, Pandanales, and Alismatales ( Figure 1; Table 2) (Cramer et al 1975;Beach 1982;Beach 1984;Young 1986;Young 1988b;Gottsberger 1989;Dieringer et al 1999;Hirthe and Porembski 2003;Maia et al 2012). In these early diverging plant groups, a wide set of floral traits and floral pollination syndromes indicate a correlation with cyclocephaline beetles (large pollen grains with sticky exudates, sturdy and funnelshaped inflorescences or large disc-shaped flowers, timing of anthesis, and thermogenesis) (Thien et al 2009;Gibernau et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, only one genus, Cyclocephala, has been recorded from dicot flowers (Figure 1). Experimental and observational studies have demonstrated that cyclocephalines can act as pollinators in Nymphaeales, Magnoliales, Arecales, Pandanales, and Alismatales ( Figure 1; Table 2) (Cramer et al 1975;Beach 1982;Beach 1984;Young 1986;Young 1988b;Gottsberger 1989;Dieringer et al 1999;Hirthe and Porembski 2003;Maia et al 2012). In these early diverging plant groups, a wide set of floral traits and floral pollination syndromes indicate a correlation with cyclocephaline beetles (large pollen grains with sticky exudates, sturdy and funnelshaped inflorescences or large disc-shaped flowers, timing of anthesis, and thermogenesis) (Thien et al 2009;Gibernau et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Some cyclocephaline/flower associations are mutualistic (Cramer et al 1975;Beach 1982;Beach 1984;Young 1986;Young 1988b;Gottsberger 1989;Dieringer et al 1999;Hirthe and Porembski 2003;Maia et al 2012). Ervik and Knudsen (2003) provide a compelling argument that scarab pollination of the Nymphaeaceae (Nymphales) is a mutualistic relationship that dates to the early Cretaceous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adult beetles use inflorescences as sites for mating and feeding, and they serve as pollinators (Moore and Jameson in press, Maia et al 2012). Species in the genus are intimately tied to host aroids and their forest habitats, and we predict that many species await discovery.…”
Section: Introductionmentioning
confidence: 99%